Village spatial planning policy in realizing a sustainable tourism village - Agus Wahyudi; Lunariana Lubis (Universitas Merdeka Malang, 2025)
The development of sustainable tourism villages necessitates the implementation of effective spatial planning policies, which are instrumental in ensuring the harmonious management of economic, social, and environmental dimensions. Kalanganyar Village, located within the Sedati Sub-district, is one of the coastal village areas in Sidoarjo Regency that has the potential to become a tourist village. The objective of this research is to analyse the spatial planning policies applied in Kalanganyar Village, Sedati Subdistrict, Sidoarjo Regency, to create a sustainable tourist village. The present research employed a qualitative methodology, utilizing a case study approach. The data collection techniques employed in this study included in-depth interviews, observational studies, and detailed documentation. The analysis techniques employed in this study are interactive, encompassing data collection, condensation, presentation, and conclusion drawing. The results indicate that the implementation of spatial planning policies in Kalanganyar Village has not contributed to the development of tourism villages. This is since these policies are not aligned with the Regional Spatial Plan (RTRW) and the Regional Medium-Term Development Plan (RPJMD) of Sidoarjo Regency. Consequently, the Village Medium-Term Development Plan (RPJMDes) and Village Government Work Plan (RKPDes) lack a clear and sustainable direction, resulting in conflicts of interest between villages and environmental damage. This research underscores the necessity of integrating spatial planning policies with local development policies to ensure targeted and sustainable development.